Perspectives on Elderly Crime and Victimization (Springer International Publishing, 2018)
This textbook focuses on the criminality and victimization of the elderly population. It provides a global perspective on the extent of elderly crime and victimization, with international comparisons for addressing the problem. It explores the extent and types of crimes committed by the elderly, the characteristics of older criminals, and the responses of the criminal justice system (including prisons and institutions) to elderly criminals, including: diversion programs, community-based treatment programs, and special programs including health & mental health care services for older prisoners. The second part of the book covers victimization of the elderly. Research findings show that certain crimes including fraud, theft, and certain types of financial crimes disproportionately affect older people, and these types of crimes are growing in prevalence. This work explores the characteristics of older victims and the types of crimes that affect them. Finally, the book presents comparative international research on approaches to crime prevention, education, and legislation to address the victimization of the elderly. This work will be of interest to students in criminology and criminal justice, as well as related fields such as sociology, and gerontology.